Citizen Participation in Sustainable Urban Development: A Framework for Engagement from the Nordics (Taylor & Francis, 2025)
This book assesses the ambitious goals for sustainability set by cities and nations and details ways to achieve those goals through effective forms of collaboration between citizens and multiple stakeholders, such as municipal decision-makers, entrepreneurs, and academic researchers. Each chapter discusses how citizens are currently involved in urban development and what opportunities there are for further deepening the collaboration in the context of urban development between citizens and municipalities. Cases from the Nordics focus on the adoption and use of digital technologies in the provision of municipal services as well as in citizen participation. The book presents the state of the art in scientific research in the field, practical examples from multiple case studies of sustainable urban development initiatives, as well as key themes for moving the discourse forward in the future. It is essential for academics, students, researchers, policymakers, urban planners, and professionals working in the areas of sustainability, urban development, and citizen engagement. It will also be relevant to citizen groups, community organisations, and activists who are interested in advocating for and participating in the development of smart and sustainable cities, particularly in Nordic countries. The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution (CC-BY) 4.0 license.